Unraveling Legitimacy: A Critical Examination of Anti-Terror Legislation in Indonesia - Riduan, Imam Malik (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
The Indonesian Law No. 5 of 2018 on the Prevention of the Criminal Acts of Terrorism, which is supposed to be the legal protection for every citizen, has generated resistance, resulting in delegitimization. This study aims to analyze the delegitimization of the anti-terrorism law, resulting in public resistance. The data was collected through observation, interviews and documentation studies in the form of the formulation of the anti-terror law. This study shows that the content of the enacted anti-terrorism law indicates a violation of human rights, which leads to delegitimization. The process of formulating the law without the participation of certain parties is considered counterproductive and makes the law less participatory. These things trigger the emergence of community resistance that leads to the failure of the law or the loss of the substance of the purpose of the legislation. As a result, the image of the government in preventing terrorism and extremism deteriorates, which in turn demonstrates the delegitimization of the law. This paper is limited to measuring the potential failure of the enactment of laws that have been passed and does not evaluate the implementation of anti-terrorism policies. Therefore, further studies are needed that focus on testing the effectiveness of the law by involving stakeholders.